Resolution of a Mobile Right Atrial Thrombus Complicating Acute Pulmonary Embolism With Low-Dose Tissue Plasminogen Activator in a Patient With Recent Craniotomy. (October 2016) - Patel, Amisha K.; Kafi, Aarya; Bonet, Antonio; Shapiro, Shelly M.; Oh, Scott S.; Zeidler, Michelle R.; Betancourt, Jaime
Right heart thrombus in transit (RHTT) is a rare, severe form of venous thromboembolism that carries a high mortality rate. The optimal treatment for RHTT has not been well established. Thrombolysis is a therapeutic modality for RHTT but carries the risk of bleeding complications including intracranial hemorrhage. Low-dose thrombolysis has been shown to be effective in treating submassive pulmonary emboli without an increased risk in bleeding complications, but it has not been studied in patients with RHTT. Here, we discuss the case of a 74-year-old male with lung cancer and recent craniotomy with metastasectomy 30 days prior to admission presenting with RHTT and bilateral pulmonary emboli (PE). He was treated successfully with low-dose thrombolysis, despite his relative contraindication to thrombolytics. To our knowledge, this is the first reported case of low-dose alteplase (tissue plasminogen activator [tPA]) used to treat an in-transit PE in the setting of recent craniotomy with metastasectomy.